2010
DOI: 10.1002/gcc.20818
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multiplex ligation‐dependent probe amplification as a method for the detection of copy number abnormalities in B‐cell precursor acute lymphoblastic leukemia

Abstract: Recent genomic studies have shown that copy number abnormalities (CNA) of genes involved in lymphoid differentiation and cell cycle control are common in B-cell precursor acute lymphoblastic leukemia (BCP-ALL). We have evaluated Multiplex Ligation-dependent Probe Amplification (MLPA) on 43 BCP-ALL patients for the detection of the most common deletions among these genes and compared the results to those obtained by fluorescence in situ hybridization (FISH) and genomic quantitative PCR (qPCR). There was good co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 20 publications
(22 reference statements)
5
100
1
4
Order By: Relevance
“…27 The dual presence of myeloid antigens CD15 (S) and CD65 (S) is, however, a feature of all CD10 NEG Blineage cases and not restricted to those with t(4;11). 20,28 Contrary to earlier reports, 12 we found CD33 and CD13 to be expressed by significantly fewer lymphoblasts in t(4;11)-positive ALL than in other Philadelphia-negative BCP-ALL. We expanded on the characteristic stem cell antigen signature of t(4;11)-positive ALL, namely CD133 high/CD34 low expression, previously proposed in pediatric ALL, 29 by showing overexpression also of CD135 and CD105, while CD123 was present though non-discriminating.…”
Section: Discussioncontrasting
confidence: 99%
“…27 The dual presence of myeloid antigens CD15 (S) and CD65 (S) is, however, a feature of all CD10 NEG Blineage cases and not restricted to those with t(4;11). 20,28 Contrary to earlier reports, 12 we found CD33 and CD13 to be expressed by significantly fewer lymphoblasts in t(4;11)-positive ALL than in other Philadelphia-negative BCP-ALL. We expanded on the characteristic stem cell antigen signature of t(4;11)-positive ALL, namely CD133 high/CD34 low expression, previously proposed in pediatric ALL, 29 by showing overexpression also of CD135 and CD105, while CD123 was present though non-discriminating.…”
Section: Discussioncontrasting
confidence: 99%
“…15 Finally, because MLPA is a technique with limited sensitivity, we selected samples with a blast burden 30%. 31,32 With this approach, we assumed that, for instance, approximately 3% of WT IKZF1 samples may have had subclonal populations with Ikaros deletions not detected by MLPA in contrast to what could have been found with polymerase chain reaction. 32 The results of the current study could help to refine the risk stratification of adolescent and adult ALL patients according to their genetic features.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these data may support the discontinuity of MEN1 intragenic deletions found in our work. Although MLPA analysis represents a powerful tool in genetic analysis being used in numerous studies (45,46), the confirmation of the observed intragenic deletions would require the subcloning of PCR products in plasmids and further sequencing. These experiments could not be performed due to scarcity of tumour tissue and large size of deletion, making it difficult to obtain a reliable PCR product from FFPE.…”
Section: Discussionmentioning
confidence: 99%